Lynx Twins with Linking Lynx: raising in captivity, capture, transport and introduction to the wild of the two Carpathian lynx (Lynx lynx carpathicus) born in the Domaine des Grottes de Han Animal Park as part of a European conservation programme - KOLTUN, ANTON (2024)
open In June of 2023 the Carpathian lynx residing in the Domaine des Grottes de Han Wildlife Park gave birth to two cubs. The following paper is a case study of those lynx cubs being prepared for the Linking Lynx reintroduction program that seeks to reinforce lynx populations across Europe as part of the EAZA conservation effort. In June of 2023 the Carpathian lynx residing in the Domaine des Grottes de Han Wildlife Park gave birth to two cubs. The following paper is a case study of those lynx cubs being prepared for the Linking Lynx reintroduction program that seeks to reinforce lynx populations across Europe as part of the EAZA conservation effort.